Z ~ 6 metal-line absorbers as a probe of galactic feedback models. Issue Volume 11:Issue S321(2015) (21st March 2017) - Keating, Laura C.; Puchwein, Ewald; Haehnelt, Martin G.; Bird, Simeon; Bolton, James S.
Abstract: Observations of metal absorption lines in the spectra of QSOs out to z > 6 are providing an important probe into the enrichment and ionization state of the intergalactic medium (IGM) at the tail end of reionization. Using simulations with four different feedback models, including the Illustris and Sherwood simulations, we investigate how the overall incidence rate and equivalent width distribution of metal-line absorbers varies with the galactic wind scheme. The low-ionization absorbers are reasonably insensitive to the feedback implementation, with all models reasonably close to the observed incidence rate of Oi absorbers. However, all of our models struggle to reproduce the observations of Civ, which is probing overdensities close to the mean at z ~ 6, suggesting that the metals are not being transported out into the IGM efficiently enough in these simulations.